1995
DOI: 10.1073/pnas.92.20.9235
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of synaptic vesicle clustering and of synaptic transmission, and increased seizure propensity, in synapsin I-deficient mice.

Abstract: Synapsin I has been proposed to be involved in the modulation of neurotransmitter release by controlling the availability of synaptic vesicles for exocytosis. To further understand the role of synapsin I in the function of adult nerve terminals, we studied synapsin I-deficient mice generated by homologous recombination. The organizaition of synaptic vesicles at presynaptic terminals of synapsin I-deficient mice was markedly altered: densely packed vesicles were only present in a narrow rim at active zones, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

24
275
2
2

Year Published

1996
1996
2007
2007

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(308 citation statements)
references
References 19 publications
(19 reference statements)
24
275
2
2
Order By: Relevance
“…Synapsin I mutant mice exhibited impairment of synaptic vesicle clustering and of synaptic transmission. Release of glutamate from nerve endings was markedly decreased in the synapsin I mutant mice (Li et al, 1995). The total synapsin (Ia, IIa, and IIIa) protein was reduced in the hippocampus of patients with bipolar disorder, another type of depression besides major depression, implying that altered or reduced synaptic function in the hippocampus may be involved in this disorder (Vawter et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…Synapsin I mutant mice exhibited impairment of synaptic vesicle clustering and of synaptic transmission. Release of glutamate from nerve endings was markedly decreased in the synapsin I mutant mice (Li et al, 1995). The total synapsin (Ia, IIa, and IIIa) protein was reduced in the hippocampus of patients with bipolar disorder, another type of depression besides major depression, implying that altered or reduced synaptic function in the hippocampus may be involved in this disorder (Vawter et al, 2002).…”
Section: Discussionmentioning
confidence: 96%
“…For instance, synapsin I, an abundant neuronal protein associated with cytoskeletal proteins and implicated in the release of neurotransmitters, is also a PIMT substrate (Paranandi and Aswad 1995). Since mice deficient in synapsin I have been reported to manifest increased susceptibility to epileptic seizures (Li et al 1995;Terada et al 1999), this protein capable of containing high levels of L-isoaspartyl residues may also play a major role in the development of epilepsy. Studies are underway to identify other PIMT substrates in human brain which may be involved in epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…deficient mice (46). A wide range of evidence, obtained from in vitro models and in vivo, has demonstrated that synapsin I is essential for the proper assembly and maintenance of presynaptic vesicle clusters (47)(48)(49)(50)(51). Interactions between synapsin I and c-Src may be of functional importance both during development and at mature synapses.…”
Section: Discussionmentioning
confidence: 99%